Geographic Information System for Fishermen's Market Kutai Kartanegara Marine and Fishery Service - Erwin Samuel Situmorang; F. V. Astrolabe Sian Prasetya; Annafi Franz (Journal of Geomatics Engineering, Technology, and Science, 2023)
Activities to process various kinds of data regarding data management are always endeavored to be ready to be presented to anyone who needs it. Geographic Information System (GIS) is an information system designed to work with spatially referenced data or geographic coordinates in other words GIS is a database system with special capabilities to handle spatially referenced data, together with a set of work operations. This study uses two methods of data collection, namely: The interview method (interview) and Document Study. The interview is a data collection method that is carried out by seeking information or data directly through sources so that the data obtained can be more accurate while conducting document studies, in document studies researchers rely on documents as one source of data to support research. The Geographic Information System of the Fishermen Market of the Kutai Kartanegara Marine and Fisheries Service was created with several programming languages Hypert Text Markup Language (HTML). The development of the system used in this study is the Waterfall model, which starts with the stages of analysis, design, coding, testing, and maintenance. The Geographic Information System of the Fisherman Market of the Kutai Kartanegara Marine and Fisheries Service aims to make it easier for service members to input fish prices and make it easier for the public to see fish prices and locations from the market.